2011
DOI: 10.1172/jci44771
|View full text |Cite
|
Sign up to set email alerts
|

mTORC1 activation in podocytes is a critical step in the development of diabetic nephropathy in mice

Abstract: Diabetic nephropathy (DN) is among the most lethal complications that occur in type 1 and type 2 diabetics.Podocyte dysfunction is postulated to be a critical event associated with proteinuria and glomerulosclerosis in glomerular diseases including DN. However, molecular mechanisms of podocyte dysfunction in the development of DN are not well understood. Here we have shown that activity of mTOR complex 1 (mTORC1), a kinase that senses nutrient availability, was enhanced in the podocytes of diabetic animals. Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
480
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 484 publications
(509 citation statements)
references
References 78 publications
26
480
2
1
Order By: Relevance
“…In addition to renal tubular cells, increased immunohistochemical staining for p62 and p-S6RP in glomerular podocytes was observed. Previous studies have shown that the activation of mTORC1 in glomerular podocytes plays a crucial role in the pathogenesis of diabetic nephropathy [25,26]. However, it remains unclear whether mTORC1 activation in podocytes contributes to the suppression of autophagy in diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to renal tubular cells, increased immunohistochemical staining for p62 and p-S6RP in glomerular podocytes was observed. Previous studies have shown that the activation of mTORC1 in glomerular podocytes plays a crucial role in the pathogenesis of diabetic nephropathy [25,26]. However, it remains unclear whether mTORC1 activation in podocytes contributes to the suppression of autophagy in diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…The mammalian target of rapamycin complex 1 (mTORC1) pathway is activated by a state of overnutrition, resulting in the suppression of autophagy. Previous reports have shown that mTORC1 activity is increased in renal cells, including tubular cells, in the diabetic state [24][25][26]. Because amino acids are recognised as mTORC1 activators [27], an LPD, which involves amino acid restriction, should suppress the mTORC1 pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Pathways contributing to podocyte injury and glomerulosclerosis (100) amongst others include the epidermal growth factor receptor (EGFR) (90), mTOR (101)(102)(103), angiotensin II (104), miR-193a (105), KLF-4 (106), adiponectin (107), RAP1GAP (82), or Rho-A (108). Apart from necrosis, apoptosis or mitotic catastrophe, migration of podocytes onto Bowman's capsule, has been suggested as a novel mechanism of podocytes loss (109,110).…”
Section: The Role Of Glomerular Cellsmentioning
confidence: 99%
“…It is the most studied regulator of autophagy; it inhibits autophagy initiation by phosphorylation of autophagy‐related proteins 5. mTOR is hyperactivated in patients with DN 6, and reduction of mTOR activity in animals suffering from diabetes mellitus (DM) suppresses DN development 7, 8.…”
Section: Introductionmentioning
confidence: 99%